2006
DOI: 10.1007/s00520-006-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors affecting the outcome of brain metastases from breast cancer

Abstract: single metastatic lesion of the brain, and brain metastases as a site of first metastases had significantly better survival in univariate analysis. Only the age during diagnosis and estrogen receptor (ER) were significantly associated with overall survival in the multivariate analysis. Patients with ER-positive disease tended to have longer overall survival compared to patients with ER-negative disease (p=0.003). Patients of 50 years of age or less tended to have longer overall survival compared to patients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…The authors observed median survival rates of 7.1, 4.2, and 2.3 months for patients who were categorized as recursive partitioning analysis class I, II, and III, respectively. Since its development, this prognostic system has been widely validated 10,21,22. In our study, women categorized as recursive partitioning analysis class I/II and III had median survival rates of 11 and 2 months, respectively ( P < .0001).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The authors observed median survival rates of 7.1, 4.2, and 2.3 months for patients who were categorized as recursive partitioning analysis class I, II, and III, respectively. Since its development, this prognostic system has been widely validated 10,21,22. In our study, women categorized as recursive partitioning analysis class I/II and III had median survival rates of 11 and 2 months, respectively ( P < .0001).…”
Section: Discussionmentioning
confidence: 73%
“…However, the prognoses of women with breast cancer and treated brain metastases vary. Several studies have reported factors that can predict for better prognosis, including younger age at brain metastases diagnosis, fewer lesions, and higher Karnofsky performance score (KPS) 9,10. In addition, stratification by Radiation Therapy Oncology Group (RTOG) recursive partitioning analysis, a classification that is based on age, KPS, and disease status, has consistently been shown to predict for prognosis, with best survival rates observed in recursive partitioning analysis class I patients and worst among recursive partitioning analysis class III patients 11…”
mentioning
confidence: 99%
“…Le caractère unique a un impact pronostique favorable (162,288). La médiane de survie est d'environ 15 mois.…”
Section: Métastase Cérébrale Uniqueunclassified